Boosting investment performance in Germany - Fuentes Hutfilter, Andrés (OECD Economics Department Working Papers, 2016)
Non-residential investment has fallen over the past 20 years as a share of GDP and is now lower than in several other high-income OECD countries. Business investment growth has been weak since the outbreak of the global financial and economic crisis. Government investment has been low, especially at municipal level. Investment in knowledge-based capital (KBC), which is closely related to long-term productivity performance, has been subdued. Weak growth prospects in the Euro Area have weighed on business investment and an increasing share of firms invests in distant, more dynamic markets. Policies that strengthen stability and growth prospects in the Euro Area would raise the attractiveness of Germany as a location to invest, notably steps to strengthen the single market and cross-border infrastructure, and complete the banking union. Steps to liberalise regulation of services, in particular knowledge-intensive professional services, would raise investment and productivity. Policies that encourage the reallocation of resources would also increase investment in KBC. Poor municipalities invest relatively little and there is scope to lower the cost of public investment projects. Better use of e-governance and more performance-oriented budgeting could improve the efficiency and effectiveness of public investment